FINANCIAL LITERACY DAN FAKTOR DEMOGRAFI PADA PELAKU USAHA KECIL MENENGAH DI MALUKU (Value : Jurnal Manajemen dan Akuntansi, 2022)
This study discusses the level of financial literacy, namely financial attitude, financial experience, and financial skills as well as the demographic factors that affected the Small and Medium Enterprises in Maluku. The purpose of this study is to measure the level of financial literacy and the demographic factors that influence SMEs in Maluku, a study of SMEs in Ambon city. The method used is descriptive statistics with a research sample of 267 SMEs in the city of Ambon. Demographic factors in this study are gender, age, income, and education level. The stages in this research are Phase I: Collecting data through literature review, observation, and interviews with SMEs. Stage 2: Managing the results of observations and interviews with SMEs and conducting data analysis that begins with data validity and reliability tests. Then, descriptive statistical tests are carried out to describe the level of financial literacy of SMEs based on financial awareness, financial experience and financial skill categories. The results showed that the level of financial literacy of SMEs in Ambon City is still relatively low. The results showed that the level of education, gender, and income per month had a significant effect on financial literacy. Education level and gender affect financial attitude. The level of education and income affect the financial experience. Gender and education level affect financial skills.Keywords: Financial Literacy, SMEs, Demographics.